KAJIAN SIMULASI COMPUTATIONAL FLUID DYNAMICS POLA ALIRAN AIR PADA TURBIN VORTEX DENGAN VARIASI TINGGI BASIN - Aghniya, Muhammad Aufa; Suarda, Made; Sukadana, I Gusti Ketut (Teknik Desain Mekanika, 2024)
Abstract Vortex turbines have the advantage of utilizing low head and have high efficiency. In addition, the vortex turbine is one example of a turbine that has easy maintenance and is friendly to the environment. In this research, the focus is on part of the vortex turbine, namely the basin height to produce optimal flow patterns and performance. The flow pattern in question is the speed contour, pressure contour, speed vector, and streamline. While the performance in question is torque, output power, and efficiency. The variation chosen in this study is the basin height variation, because in the basin vortex flow occurs and the basin height affects the speed of the vortex flow that occurs. The purpose of this research is to determine the flow pattern and performance of the vortex turbine by varying the basin height. This research will conduct Computational Fluid Dynamic simulation testing, namely Ansys fluent. The simulation results show that the basin height affects the flow pattern and performance of the turbine. In the simulation results, the basin height of 390mm has the highest efficiency value of 10.72%. While the lowest efficiency value is found at a basin height of 430mm with an efficiency value of 8.1%. To increase the efficiency of this vortex turbine can consider the height of the basin with the inlet and outlet of the basin Keywords: Computational Fluid Dynamic. Height of basin, Vortex turbine, Flow patterns, turbine performance